(Prediction of Vaporization Latent Heat of White and Black Pepper Beans (Piper Ningrum L.) for Drying Application) - Lamhot P. Manalu; Rizal Alamsyah (Warta Industri Hasil Pertanian, 2008)
In most drying application the latent heat is determinaned by considering the evaporation of free water as given in the steam tables. The use of these data for latent heat, especialy with crop at a low moinsture content, present considerable error. The equalibrium moinsture data may be used as a basis for determining the latent heat. Experiment was carried out by drying pepper beans to remove its moinsture at some temperature levels (35,45,55 and 65.